Elevated serum uric acid levels are independent risk factors for diabetic foot ulcer in female Chinese patients with type 2 diabetes (血尿酸水平升高是中国女性2型糖尿病患者糖尿病足溃疡的独立危险因素). (2nd September 2013) - Ye, Xiao; Cao, Ying; Gao, Fang; Yang, Qunying; Zhang, Qian; Fu, Xiajun; Li, Jimin; Xue, Yaoming
Abstract Background To investigate the relationship between elevated serum uric acid levels and the presence of diabetic foot ulcer (DFU) in Chinese patients with type 2 diabetes (T2D). Methods A retrospective study was performed on 829 outpatients with T2D (478 men, 351 women) who visited the Diabetes Clinic (Nanfang Hospital, Southern Medical University) from January 2007 to December 2009. Information regarding their clinical history, anthropometric measurements, and laboratory data were collected. Potential confounding variables with P < 0.10 were adjusted for in multivariate logistic regression analysis. Results In univariate analyses, there was a significant difference in serum uric acid levels between female patients with and without DFU (370 ± 128 vs. 313 ± 107 μmol/L, respectively; P < 0.05), but not between male patients with and without DFU (317 ± 100 vs. 348 ± 111 μmol/L, respectively; P = 0.643). The prevalence of DFU among quintiles of uric acid levels (from 1–20% to 80–100%) was 5.3%, 3.9%, 7.7%, 5.5%, and 16.7%, respectively. Using uric acid level as a continuous variable, the multivariate‐adjusted odds ratio for diabetic foot ulcer in female patients was 1.004 (95% confidence interval 1.001–1.008; P < 0.05). Conclusions Elevated uric acid levels are a significant and independent risk factor for diabetic foot ulcer in female Chinese patients with T2D. Whether serum uric acid is involved in the pathogenesis of DFU in female patients remains to be investigated.